AHNAK2: a potential diagnostic biomarker for pancreatic cancer related to cellular motility - Mohamed Zardab; Barts Pancreas Tissue Bank; Richard P. Grose; Hemant M. Kocher (Scientific Reports)
Abstract Pancreatic ductal adenocarcinoma lacks suitable biomarkers for early diagnosis of disease. In gene panels developed for early diagnosis of pancreatic cancer, high AHNAK2 mRNA expression was one possible biomarker. In silico analysis of published human sample datasets (n = 177) and ex vivo analysis of human plasma samples (n = 30 PDAC with matched 30 healthy control) suggested AHNAK2 could be a diagnostic biomarker. At a plasma level of 421.47 ng/ml, AHNAK2 could potentially diagnose PDAC with a specificity and sensitivity of 83.33% and 86.67%. In vitro analysis suggests that in cell lines with diffuse cytoplasmic distribution of AHNAK2, there was colocalization of AHNAK2 with Cortactin in filipodia. This colocalization increased when cells were cultured on substrates such as Fibronectin and Collagen, as well as in hypoxia, and resulted in an augmented invasion of cancer cells. However, in cell lines with a vesicular AHNAK2 staining, such changes were not observed. Our study posits AHNAK2 as a valuable diagnostic biomarker in PDAC, now demanding prospective validation. Determination of mechanisms regulating AHNAK2 subcellular localisation may help explain its biological role.